The Profit Motive in Education: Continuing The Revolution - Ed. Stanfield, James B (Institute of Economic Affairs, 2012)
The Uk government - in common with the governments of many Western countries - is in the midst of implementing policies to reform Education.
Keywords: Education; Non Fiction; Revolution